The role of continuing teacher training in the office of governing secondary schools in tierra del fuego, antarctica and south atlantic islands - Paez, Luis Ricardo; Abendaño López, Sandra (Servicio de Publicaciones de la Universidad Pontificia de Salamanca, 2021)
The purpose of this article is to communicate partial results of the research project “The office of governing secondary schools in the province of Tierradel Fuego, Antarctica and the South Atlantic Islands (AeIAS) of the Argentine Republic” directed by Mg. Méndez María José, from the National University of Tierra del Fuego, AeIAS. It will focus on the specific objective of “Analyzing the role of continuing teacher training around the office of governing TDF AeIAS secondary schools”. Based on the analysis of individual interviews, focus groups and national and provincial regulations, the meanings that management teams give to continuous teacher training around the office of governing secondary level institutions and the conditions of access to schools are described. handling fees. The results refer to continuous training for the government of secondary schools as a complex construction and to the provincial debt of linking access to management positions with continuous training for the exercise of the role. El presente artículo tiene como finalidad comunicar resultados parciales del proyecto de investigación “El oficio de gobernar colegios secundarios en laprovincia de Tierra del Fuego, Antártida e Islas del Atlántico Sur (AeIAS) de la República Argentina” dirigido por la Mg. Méndez María José, de la Universidad Nacional de Tierra del Fuego, AeIAS. Se focalizará en el objetivo específico de “Analizar el rol de la formación docente continua en torno al oficio de gobernar los colegios secundarios de TDF AeIAS”. A partir del análisis de entrevistas individuales, grupos focales y normativa nacional y provincial, se describen los sentidos que los equipos de gestión le otorgan a la formación docente continua en torno al oficio de gobernar las instituciones de nivel secundario y a las condiciones de acceso a los cargos de gestión. Los resultados refieren a la formación continua para el gobierno de los colegios secundarios como una construcción compleja y a la deuda provincial de vincular el acceso a los cargos de ...